2019
DOI: 10.1016/j.carj.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extramural Venous Invasion by Diffusion-Weighted Magnetic Resonance Imaging and Computed Tomography in Rectal Adenocarcinoma

Abstract: Purpose The aim of this study is to evaluate the diagnostic contribution of diffusion-weighted magnetic resonance imaging (MRI) and computed tomography (CT) to distinguish extramural venous invasion (EMVI) in rectal adenocarcinoma. Materials and Methods Fifty-eight patients who had been diagnosed with rectal adenocarcinoma (30 patients with EMVI and 28 patients without EMVI) were enrolled in the study. Apparent diffusion coefficient (ADC) values of the tumour and the EMVI (+) vein, the lengths of the tumours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Only 3 studies were prospective in nature, 8,24,25 with the remaining 14 being retrospective cohorts 26–39 . A total of 3821 patients were involved in this review and the entire cohort spanned from 2000 to 2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 3 studies were prospective in nature, 8,24,25 with the remaining 14 being retrospective cohorts 26–39 . A total of 3821 patients were involved in this review and the entire cohort spanned from 2000 to 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Only 3 studies were prospective in nature, 8,24,25 with the remaining 14 being retrospective cohorts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] A total of 3821 patients were involved in this review and the entire cohort spanned from 2000 to 2017. Table 1 summarizes the characteristics of included studies.…”
Section: Literature Search and Description Of Studiesmentioning
confidence: 99%
“…Gursoy et al. ( 50 ) had suggested that the ADC value was associated with EMVI diagnosis of rectal adenocarcinoma. We conducted further inter-group comparison of patients in 5 groups with different EMVI scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with CT radiation damage, nomogram may be more suitable for clinical practice. Aysegul et al Used changes in dimensions of superior recurrent vein (SRV) and inferior median vein (IMV) and ADC values were used to predict EMVI (39), and the AUC values were 0.851.0.893 and 0.664, respectively. Although the diagnostic efficiency of IMV was higher than that of the nomogram, but these indexes were based on CT examination, while the ADC value based on MRI examination was significantly lower than that of our nomogram.…”
Section: Discussionmentioning
confidence: 99%